Golput dalam Pemilihan Gubernur Provinsi Jambi Tahun 2020 - Muhammad Farhan HR (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
This research aims to analyze the causes of the phenomenon of abstention and the level of community participation in the election of the Governor of Jambi Province in 2020. The study adopts a qualitative approach with a literature review as the methodology. Data collection is conducted through various sources such as books, journals, magazines, newspapers, and others. The use of the Concept Map feature in NVIVO12 Plus is also part of the research methodology. The research findings indicate that the level of community participation in the election of the governor in 2020 in Jambi Province reached 1,658,525 eligible voters. Out of this number, 1,570,285 votes were considered valid, while 88,240 votes were deemed invalid. Non-participating voters (abstention) amounted to 820,779 out of a total of 2,480,612 registered voters. Kerinci Regency had the highest abstention rate, where out of a total of 198,729 registered voters in the Permanent Voter List, 88,637 individuals (44.60%) chose to abstain. Several factors, including differences in the ethnic backgrounds of the candidates, educational levels, inadequate quality of candidates, political practices, apathetic attitudes of the community, lack of information, technical constraints, and the inaccessibility of polling locations influenced the phenomenon of abstention in the 2020 Jambi gubernatorial election.